Analysis of the Effect of Population, Average Years of Schooling, and Per Capita Expenditure on Income Inequality among 14 Regencies/Cities in Kalimantan Barat Province - Ihsan, Muhammad Nurul; Tamtama, Ray; Supandi, Supandi (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
In the implementation of economic development, Indonesia as a developing country is faced with complex problems in the implementation of economic development that is currently being carried out, namely the problem of inequality in income distribution. In West Kalimantan Province itself, regional economic development still needs special attention, in order to narrow the possibility of regional income inequality. One important aspect of economic development is improving the standard of living of the people. Improvements from social, educational and economic aspects must be made. In this research, data variables will be used that represent these aspects, namely population, average years of schooling, and per capita expenditure, which will then be identified using panel data regression analysis with best estimation modeling to determine the influence of these variables. on the Gini Ratio figure as a measuring variable of income inequality between 14 districts/cities in West Kalimantan Province from 2012 to 2023. Panel data regression in this research is used as an analytical tool using the best estimation modeling, namely the Fixed Effect Model (FEM). From the results of the analysis carried out, it was found that population size has a significant influence on the Gini Ratio figure. Meanwhile, the average years of schooling and per capita expenditure do not have a significant influence on the Gini Ratio or income inequality in West Kalimantan Province.